Shale-hosted biota from the Dismal Lakes Group in Arctic Canada supports an early Mesoproterozoic diversification of eukaryotes. (November 2021) - Loron, Corentin C.; Halverson, Galen P.; Rainbird, Robert H.; Skulski, Tom; Turner, Elizabeth C.; Javaux, Emmanuelle J.
Abstract: The Mesoproterozoic is an important era for the development of eukaryotic organisms in oceans. The earliest unambiguous eukaryotic microfossils are reported in late Paleoproterozoic shales from China and Australia. During the Mesoproterozoic, eukaryotes diversified in taxonomy, metabolism, and ecology, with the advent of eukaryotic photosynthesis, osmotrophy, multicellularity, and predation. Despite these biological innovations, their fossil record is scarce before the late Mesoproterozoic. Here, we document an assemblage of organic-walled microfossils from the 1590–1270 Ma Dismal Lakes Group in Canada. The assemblage comprises 25 taxa, including 11 morphospecies identified as eukaryotes, a relatively high diversity for this period. We also report one new species, Dictyosphaera smaugi new species, and one unnamed taxon. The diversity of eukaryotic forms in this succession is comparable to slightly older assemblages from China and is higher than worldwide contemporaneous assemblages and supports the hypothesis of an earlier diversification of eukaryotes in the Mesoproterozoic.